Bamboo-Leaf Prickly Ash extract: A potential bio-pesticide against oriental leaf worm, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae). (15th February 2018) - Kaleeswaran, G.; Firake, D.M.; Sanjukta, R.; Behere, G.T.; Ngachan, S.V.
Abstract: Bamboo-Leaf Prickly Ash, Zanthoxylum armatum (Rutaceae) is a versatile and widely distributed plant species in nature. It is an edible plant species, commonly used in daily life for condiments and therapeutic remedies. Besides its bioactive and medicinal properties, different plant parts of the Z. armatum also have insecticidal potential. However, this potential has not been yet determined against many agricultural pests, including leaf worm, Spodoptera litura (Lepidoptera: Noctuidae). In this study, we demonstrated for the first time the contact and oral toxicity and sub-lethal effects (including antifeedent and ovicidal action) of various fractions of pericarp, leaf and seeds of Z. armatum against S. litura. Overall findings revealed that the n-hexane pericarp extract of Z. armatum has strong antifeedent, ovicidal and larvicidal properties against S. litura . Sub-lethal doses of pericarp extract can negatively alter the biology of S. litura . Since n-hexane extract of leaves also has better larvicidal properties, it could also be utilized for the S. litura management during period of unavailability of fruits (or pericarp). Accordingly, the Z. armatum pericarp and leaf extract has tremendous commercial utilization potential for the management of polyphagus pests like S. litura and other related species, which are quite difficult to manage even by chemical pesticides. Highlights: Insecticidal potential of different plant parts of Zanthoxylum armatum (ZA) demonstrated against Spodoptera litura (SL). N-hexane pericarp extract (PE) of ZA has strong antifeedent, ovicidal and larvicidal properties against SA. N-hexane leaf extract (LE) of ZA also have larvicidal properties. Sub-lethal doses of PE can negatively alter the biology of SL. ZA extract has tremendous potential for its commercial utilization for the management of SL.